Peranan Pola Asuh Orang Tua Dalam Membentuk Perilaku Transeksual dan Pengukuran Diri Ekspresi Pelajar Transeksual (Studi Kasus di Malaysia) - Kurniawan, Yohan; Kusumawardhani, Naftalia; Apsari, Yuni; Yusof, Aminuddin Md (ANIMA Indonesian Psychological Journal, 2002)
Transexuality is one of the abnormal problems faced by adolescent and adults. The problem is felt in universities in Malaysia. The present study attempts to examine the abnormalities faced by transexuals as compared to normal subject. Subjects were 3 students with transexual problem and 3 normal students. Subject were asked to draw a man. Drawings made by normal and abnormal persons were compared. The study showed that there was a difference in terms of gender of the persons drawings. Transexuals tend to draw woman photographs. Students with transexual problems tend to view women as representing their selves which is in contrast to normal students who tend to draw a person according to his own gender. Transexual students was found to go through the same socialisation process of gender role as those experienced by women.